A Review on GPU Programming Strategies and Recent Trends in GPU Computing - Chandran S., Nisha; Gangodka, Durgaprasad; Mittal, Ankush (Journal of Graphic Era University, 2023)
<span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*307.97px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.905847);" role="presentation">The advancements in the field of internet and cloud computing has resulted in a huge am<span dir="ltr" style="left: calc(var(–scale-factor)*427.39px); top: calc(var(–scale-factor)*307.97px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.925888);" role="presentation">ount of multimedia data <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*321.17px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.92668);" role="presentation">and processing of this data have become more complex and computationally intensive. <span dir="ltr" style="left: calc(var(–scale-factor)*430.99px); top: calc(var(–scale-factor)*321.17px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.952017);" role="presentation">With the advent of the <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*334.37px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.879609);" role="presentation">scalable, <span dir="ltr" style="left: calc(var(–scale-factor)*110.06px); top: calc(var(–scale-factor)*334.37px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.92198);" role="presentation">inexpensive Graphics Processing Units (GPUs) <span dir="ltr" style="left: calc(var(–scale-factor)*306.17px); top: calc(var(–scale-factor)*334.37px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.957636);" role="presentation">with very high computation power, <span dir="ltr" style="left: calc(var(–scale-factor)*453.46px); top: calc(var(–scale-factor)*334.37px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.920516);" role="presentation">the processing of <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*347.69px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.964624);" role="presentation">such big data has <span dir="ltr" style="left: calc(var(–scale-factor)*152.18px); top: calc(var(–scale-factor)*347.69px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.933937);" role="presentation">become less expensive and <span dir="ltr" style="left: calc(var(–scale-factor)*271.97px); top: calc(var(–scale-factor)*347.69px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.967404);" role="presentation">efficient. <span dir="ltr" style="left: calc(var(–scale-factor)*312.65px); top: calc(var(–scale-factor)*347.69px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.969262);" role="presentation">Also <span dir="ltr" style="left: calc(var(–scale-factor)*336.31px); top: calc(var(–scale-factor)*347.69px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.987113);" role="presentation">fast developments happening in the field of <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*360.89px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.9117);" role="presentation">programming languages and different <span dir="ltr" style="left: calc(var(–scale-factor)*225.65px); top: calc(var(–scale-factor)*360.89px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.913039);" role="presentation">programming and debugging <span dir="ltr" style="left: calc(var(–scale-factor)*344.71px); top: calc(var(–scale-factor)*360.89px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.904554);" role="presentation">tools adds to the ease of GPU programming. <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*374.09px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.936903);" role="presentation">However, utilizing the resources of the GPU effectively and fully is still a challenge. <span dir="ltr" style="left: calc(var(–scale-factor)*415.27px); top: calc(var(–scale-factor)*374.09px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.919391);" role="presentation">The goal of this paper is to <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*387.29px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.868203);" role="presentation">present a <span dir="ltr" style="left: calc(var(–scale-factor)*111.02px); top: calc(var(–scale-factor)*387.29px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.952098);" role="presentation">brief review of NVIDIA’s state of the art Fermi architecture and <span dir="ltr" style="left: calc(var(–scale-factor)*374.35px); top: calc(var(–scale-factor)*387.29px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.920844);" role="presentation">to survey <span dir="ltr" style="left: calc(var(–scale-factor)*414.31px); top: calc(var(–scale-factor)*387.29px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.960409);" role="presentation">different p<span dir="ltr" style="left: calc(var(–scale-factor)*456.70px); top: calc(var(–scale-factor)*387.29px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.927976);" role="presentation">rogramming <span dir="ltr" style="left: calc(var(–scale-factor)*508.90px); top: calc(var(–scale-factor)*387.29px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.86296);" role="presentation">and <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*400.51px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.948777);" role="presentation">optimization <span dir="ltr" style="left: calc(var(–scale-factor)*125.30px); top: calc(var(–scale-factor)*400.51px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.872624);" role="presentation">strategies <span dir="ltr" style="left: calc(var(–scale-factor)*165.74px); top: calc(var(–scale-factor)*400.51px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.903662);" role="presentation">adopted by researchers’ to accelerate the GPU computation. <span dir="ltr" style="left: calc(var(–scale-factor)*410.47px); top: calc(var(–scale-factor)*400.51px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.916629);" role="presentation">This survey a<span dir="ltr" style="left: calc(var(–scale-factor)*464.86px); top: calc(var(–scale-factor)*400.51px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(1.0113);" role="presentation">ims <span dir="ltr" style="left: calc(var(–scale-factor)*482.14px); top: calc(var(–scale-factor)*400.51px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.938858);" role="presentation">to provide <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*413.83px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.919091);" role="presentation">researchers with knowledge about the different programming and optimization techniques in GPU programming <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*427.03px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(1.0312);" role="presentation">and to motivate them to <span dir="ltr" style="left: calc(var(–scale-factor)*185.18px); top: calc(var(–scale-factor)*427.03px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(1.01033);" role="presentation">architect highly efficient parallel algorithms by extracting maximum available <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*440.23px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.925861);" role="presentation">capability of the GPUs. <span dir="ltr" style="left: calc(var(–scale-factor)*168.38px); top: calc(var(–scale-factor)*440.23px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.886113);" role="presentation">The paper <span dir="ltr" style="left: calc(var(–scale-factor)*211.25px); top: calc(var(–scale-factor)*440.23px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.878246);" role="presentation">also <span dir="ltr" style="left: calc(var(–scale-factor)*229.85px); top: calc(var(–scale-factor)*440.23px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.916735);" role="presentation">explores <span dir="ltr" style="left: calc(var(–scale-factor)*266.21px); top: calc(var(–scale-factor)*440.23px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.856168);" role="presentation">some <span dir="ltr" style="left: calc(var(–scale-factor)*289.61px); top: calc(var(–scale-factor)*440.23px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.921393);" role="presentation">recent trends in the field of GPU programming.